Biosimilars for psoriasis: clinical studies to determine similarity. (1st July 2017) - Blauvelt, A.; Puig, L.; Chimenti, S.; Vender, R.; Rajagopalan, M.; Romiti, R.; Skov, L.; Zachariae, C.; Young, H.; Prens, E.; Cohen, A.; van der Walt, J.; et al.
Summary: Biosimilars are drugs that are similar, but not identical, to originator biologics. Preclinical analytical studies are required to show similarity on a molecular and structural level, but efficacy and safety studies in humans are essential to determining biosimilarity. In this review, written by members of the International Psoriasis Council, we discuss how biosimilars are evaluated in a clinical setting, with emphasis on extrapolation of indication, interchangeability and optimal clinical trial design.